Implementação de políticas de gestão de pessoas do estado de Minas Gerais: uma análise das políticas avaliação de desempenho individual e certificação ocupacional - Kamila Pagel de Oliveira (2016)
Studies on implementation of public policies show many problems to the effectiveness of policies and factors that can increase the success of public policies. There are several factors that influence the implementation of public policies, among them can be cited: the politicalcontent, implementation context, commitment of involved, institutional and administrative capacity and power to influence the implementers and the target audience (LIPSKY, 1980; PETER, 1998; BRYNARD, 2000, SIMAN, 2005; DYE, 2008; O'Toole, 2010; RADIN, 2010; TUMMERS, 2012). As a result, it is observed in practice that the performance of these policies is often lower than planned (FREY, 2000; SIMAN, 2005). When implementing policies involves inter-organizational contexts, implementation challenges become even greater in view of the different actors, interests and values, rules and routines, levels of information and resource (O'TOOLE, 2010; RADIN 2010 ). The State of Minas Gerais, since 2003, has implemented a number of policies regarding the management of human resource, including the Individual Performance Assessment, implemented in 2004 in order to monitor the supply of each server, aiming the improvement of institutional results and OccupationalCertification, implemented in 2007 in order to recruit and allocate people who have proven technical and behavioral skills appropriate to the wide recruiting positions mining executive. Both policies were implemented in inter-organizational context, as they were formulated by the State Secretariat Planning of the State of Minas Gerais, however, implemented not only through this Secretariat, but also by other state organs and entities, as is the if the Secretary of State for Social Defense (SEDS) and the State Secretariat of Education (SEE), chosen for analysis. In this context, the present work had as main objectives the analysis of humanresource management model adopted in Minas Gerais since 2003, and the analysis of policy implementation Individual Performance Assessment and Occupational Certification in both Secretariat, considering the instruments and strategies used and the results of implementation. Regarding the human resource management model, it is clear that despite the progress made since 2003, Minas Gerais has an operational model, not only due to the activities still performed by this area, but also by the lack of adequate investment the management of human resource, considering financial, human and material. Regarding the implementation of ADI and CO policies, although there are specific to each one, it is perceived failures and difficulties regarding: the content of the policy (for ADI only); the institutional context; administrative capacity of implementers; the participation of implementers and target audience of policies; and the commitment theirs in the implementation of policies. The main problems of implementation related to ADI and CO policies are: i) the centralized model by which policies were formulated, excluding the participation of implementers and target audience of policy; ii) the inexperience of formulators and implementers, as both these wereinnovative policies in the context of the Brazilian government; iii) little importance given to institutional arrangements and operational capacity of sector agencies, as a requirement for the effective implementation of policies.